2020
DOI: 10.1159/000508537
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Mammary Calciphylaxis in a Patient on Long-Standing Renal Dialysis

Abstract: • Calciphylaxis (calcific uremic arteriopathy) is a rare medical condition characterised by ectopic deposition of calcium in arterioles in patients with long-standing renal conditions. • The pathogenesis is related to impaired calcium metabolism. • Calcium deposition commonly occurs in skin and has been described in the breast mimicking ulcerating breast cancer. Novel Insights • Calciphylaxis may present on imaging as calcifications, a spiculated mass, or distortion and may mimic a malignancy. • The lesion sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…While most commonly seen on the abdomen and proximal lower extremities, calciphylaxis has been reported in relatively uncommon sites including the penis, breasts, and digits. [26][27][28][29][30] The presence of ulceration is associated with an increased mortality rate (Figure 3). 31 Visceral calciphylaxis without primary cutaneous manifestations has also been reported, such as in mesenteric and colonic arteries .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…While most commonly seen on the abdomen and proximal lower extremities, calciphylaxis has been reported in relatively uncommon sites including the penis, breasts, and digits. [26][27][28][29][30] The presence of ulceration is associated with an increased mortality rate (Figure 3). 31 Visceral calciphylaxis without primary cutaneous manifestations has also been reported, such as in mesenteric and colonic arteries .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Of these, one study found that while the presence of vascular calcification had the highest sensitivity for calciphylaxis (89.2, CI = 73.0 -100), a netlike pattern of calcification exhibited the greatest specificity (89.9, CI = 82.7 -97). 28,45 Point-of-care ultrasound (POCUS) may also aid in diagnosis. Sonographic characteristics that have been associated with calciphylaxis include the presence of thin hyperechoic bands parallel J o u r n a l P r e -p r o o f 9 to the epidermal surface generating a strong posterior acoustic shadow, hyperechoic spots with a narrow acoustic window, and linear hyperechoic bands parallel to the walls of a blood vessel with a narrow acoustic shadow.…”
Section: Diagnosis Of Calciphylaxismentioning
confidence: 99%
“…Calcifications can arise rapidly within several months, such that negative radiological evaluations in the past medical history cannot reliably rule out de novo ectopic deposition of calcium deposits [ 4 ]. In extremely rare cases, ectopic tumoral calcinosis has been described in multiple distinct locations in the same patient [ 2 ] and concomitantly with calciphylaxis [ 5 ]. Nevertheless, in contrast to calciphylaxis, ectopic calcifications are not associated with warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Painful evolving skin lesions (livedo reticularis, livedo racemosa, and retiform purpura) typically involving the areas of cutaneous and subcutaneous adiposity and rapidly progressing to ulcers with black eschar are the hallmarks of calciphylaxis presentation [9]. Although reported in relatively uncommon sites, including the penis, the digits, and the breasts [10][11][12][13], the lesions are most commonly seen on the abdomen and proximal lower extremities.…”
Section: Introductionmentioning
confidence: 99%